Less is More: Eliminating Index Terms from Subordinate Clauses - Corston-Oliver, Simon H.; Dolan, William B.; Dolan, Bill (Association for Computational Linguistics, 1999)
We perform a linguistic analysis of documents during indexing for information retrieval. By eliminating index terms that occur only in subordinate clauses, index size is reduced by approximately 30% without adversely affecting precision or recall. These results hold for two corpora: a sample of the world wide web and an electronic encyclopedia.